The Urgency of Karen Armstrong Compassion Value in the Context of Religious Pluralism at SMP Negeri 2 Sentani - Himber, Abjanli; Labobar, Bernard; Malatuny, Yakob Godlif (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2024)
This research highlights the importance of implementing Karen Armstrong's compassion values at SMP Negeri 2 Sentani to support harmony in religious diversity. Compassion must be taught in a pluralist educational environment to form empathy and strong character from an early age. Given the limited understanding of pluralism among students and the lack of integration of compassion values in the curriculum, this study aims to explore effective strategies in instilling these values. The method used was qualitative research with data collection through observation and in-depth interviews. The results showed that the value of compassion could increase mutual respect and support among students, which is realized through collaborative activities such as religious holiday celebrations and interfaith prayers. Teachers are essential in internalizing compassion through narrative, discussion, and cooperative learning approaches. In conclusion, implementing the value of compassion at SMP Negeri 2 Sentani not only creates a harmonious and safe environment but also forms a young generation that can live peacefully amid religious differences, showing that differences are strengths that can be embraced together.